Performance measures and worker productivity - Jan Sauermann (IZA World of Labor, 2016)
Measuring workers' productivity is important for public policy and private-sector decision-making. Due to a lack of reliable methods to determine workers' productivity, firms often use specific performance measures, such as how different incentives affect employees' behavior. The public sector also uses these measures to monitor and evaluate personnel, such as teachers. To select the right performance measures, and as a result design better employment contracts and improve productivity, policymakers and managers need to understand the advantages and disadvantages of the available metrics.
Keywords: J24; M12; D24; 330; worker productivity; performance measures; human resource management